The Principle of Legal Protection in the Provision of Emergency Contraception Services for Rape Victims under Law 36 of 2009 on Health - Fitrianti, Mia Yulia; Fakhriah, Efa Laela; Handayani, Tri (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Rape, a violent act involving coerced sexual intercourse, necessitates the provision of emergency contraception services to prevent unwanted pregnancies. Competent and authorized healthcare professionals are responsible for delivering these services, which are governed by government regulations in accordance with the health law. Thus, the author explores the legal protection that emergency contraception services offer to both rape victims and healthcare providers, highlighting the underlying principles of this implementation. This research employs a descriptive analysis using a normative juridical approach. Findings indicate several barriers to service provision, including limited doctor knowledge, inadequate standard operating procedures, and exclusion from the hospital's essential medicine formulary. Emergency contraception services are legally regulated as part of the Health Law, as they fulfill the legal needs of rape victims, surpassing the hierarchy of Government Regulations. By preventing unwanted pregnancies without the need for complicated procedures like abortion, emergency contraception services significantly enhance the protection of rape victims and healthcare workers. However, the current regulations lack provisions mandating the provision of information and emergency contraception services to rape victims by healthcare providers. Consequently, not all healthcare workers are willing to offer these services due to the absence of legal obligations. To ensure the availability of emergency contraception services, legislative changes should be made by introducing new articles into the health law, explicitly stating the obligation of healthcare providers to offer emergency contraception services to rape victims.